Influence of the type of photocatalyst on photocatalytic oxidation of triclosan in the aquatic environment. (17th January 2022) - Zawadzki, Piotr; Kudlek, Edyta; Dudziak, Mariusz
A comparative assessment of triclosan removal (an antibacterial compound) in aqueous solutions at a concentration of 1.0 mg/dm 3 during an advanced oxidation process in the presence of commercial titanium dioxide (TiO2 ) and photocatalysts modified with the powdered activated carbon and ultrasounds was studied. Photocatalytic processes were examined using a photocatalyst at the dose concentration of 100 mg/dm 3 . The influence of photocatalysts modification on triclosan sorption process and its decomposition was found. Triclosan was adsorbed in the range of 69% to 96%. After 20 minutes of the photocatalysis, triclosan decomposition was set to 91% in the presence of pure TiO2 . For the modified photocatalysts, the removal degree exceeded 99% after 10 minutes of irradiation. The Langmuir-Hinshelwood model was used to describe the kinetics of triclosan degradation. Reaction kinetics showed a two-stage oxidation process in the presence of a photocatalyst modified with activated carbon and ultrasounds.